2014
DOI: 10.1371/journal.pone.0104616
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Ameliorates Neuropathological Changes, TGF-β1 Accumulation and Behavioral Deficits in a Mouse Model of Cerebral Amyloidosis

Abstract: Icariin, a major constituent of flavonoids from the Chinese medicinal herb Epimedium brevicornum, exhibits multiple biological properties, including anti-inflammatory, neuroregulatory and neuroprotective activities. Therefore, Icariin might be applied in treatment of neurodegenerative disorders, including Alzheimer's disease (AD), which is neuropathologically characterized by β-amyloid aggregation, hyperphosphorylated tau and neuroinflammation. Potential therapeutic effects of Icariin were investigated in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…In research of Li F et al, ICA has instigated the improvement of memory function, as well as reducing Aβ and APP levels in the brain [3]. A similar conclusion was made by Zhang ZY et al, assessing the effect of Icariin onan animal model of cerebral amyloidosis for AD in transgenic APP/PS1 mouse [6]. In the study by Zhang, L. et al, in addition, there was a reduction in β-amyloid burden, and a decrease in APP, and beta-site amyloid precursor protein cleaving enzyme 1 (BACE-1) expression was observed in the transgenic mouse APP model of AD [7].…”
Section: Methodsmentioning
confidence: 62%
“…In research of Li F et al, ICA has instigated the improvement of memory function, as well as reducing Aβ and APP levels in the brain [3]. A similar conclusion was made by Zhang ZY et al, assessing the effect of Icariin onan animal model of cerebral amyloidosis for AD in transgenic APP/PS1 mouse [6]. In the study by Zhang, L. et al, in addition, there was a reduction in β-amyloid burden, and a decrease in APP, and beta-site amyloid precursor protein cleaving enzyme 1 (BACE-1) expression was observed in the transgenic mouse APP model of AD [7].…”
Section: Methodsmentioning
confidence: 62%
“…7E ]. Our previous results [16] showed a significant reduction in plaque numbers in the cortex of icariin- and hesperidin-treated mice [experiment Ⅱ, control Ⅱ=149.0 (128.5–197.8), icariin=100.5 (61.8–130.3), P ≤0.05, Fig. 7C ; experiment Ⅲ, control Ⅲ=157.0 (147.0–169.3), hesperidin=126.0 (103.0–142.0), P ≤0.05, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Icariin, a main constituent of Epimedii Herba and a well-known tonic crude drug, has been found to have a remarkable effect on AD in the past 10 years. Researchers found that icariin could reduce the Aβ burden and amyloid plaque deposition in the hippocampus of AD transgenic mice, 36,50,51 and preserve the expression of synaptic functional proteins and improve synaptic function. 42 Ginsenoside could attenuate pathological tau phosphorylation 37 and ameliorate hippocampal Aβ deposition in AD mice.…”
Section: Discussionmentioning
confidence: 99%